2004
DOI: 10.1038/sj.bmt.1704795
|View full text |Cite
|
Sign up to set email alerts
|

A novel reduced-intensity stem cell transplant regimen for nonmalignant disorders

Abstract: Summary:Bone marrow transplantation (BMT) benefits nonmalignant diseases but is limited by regimen-related toxicity, graft-versus-host disease (GVHD), donor availability, and graft rejection (GR). To overcome some of these barriers, we developed a new conditioning strategy for these patients. In total, 16 patients received Campath-1H (33/ 48 mg; days À21 to À19), fludarabine (150 mg/m 2 ; days À8 to À4), melphalan (140/70 mg/m 2 ; day À3), and transplant using related/unrelated stem cells. GVHD prophylaxis inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 45 publications
2
110
1
Order By: Relevance
“…However, fatal infectious complications were common, and overall survival was 75%. 26 Del Toro et al reported their results using RIC in 21 children with malignant and nonmalignant disorders. They used three different fludarabine-based regimens and unrelated cord blood and matched family donors.…”
Section: Discussionmentioning
confidence: 99%
“…However, fatal infectious complications were common, and overall survival was 75%. 26 Del Toro et al reported their results using RIC in 21 children with malignant and nonmalignant disorders. They used three different fludarabine-based regimens and unrelated cord blood and matched family donors.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure used to be rarely considered by the hematology community due to toxicity and mortality risks, but is now more acceptable with RIT regimens that are better tolerated. 28 The paucity of minority donors in the registry often limits finding a suitable MUD in this population. 29 The probability of finding a matched marrow or cord product for SCD patients depends on the level of mismatching that is considered acceptable.…”
Section: Scope Of the Disease In Relation To Transplantation And Timingmentioning
confidence: 99%
“…53 Graft rejection (5%) and GVHD rates (15% acute; 11% chronic) were low in 62 non-malignant disorder transplants. Initial experience with 11 hemoglobinopathy transplants showed that the regimen was well tolerated and supported engraftment of related and unrelated donor cells when the melphalan dose was 140 mg/m 2 but not 70 mg/m 2 .…”
Section: Preparative Regimenmentioning
confidence: 99%